Auditor-provided tax services and stock price crash risk. Issue 1 (2nd January 2016) - Habib, Ahsan; Hasan, Mostafa Monzur
Abstract : This paper examines whether auditor-provided tax services affect stock price crash risk: an important consideration for stock investors. Provision of tax services by incumbent auditors could accentuate or attenuate crash risk depending on whether such services give rise to knowledge spillover or impair auditor independence. The study investigates two channels through which tax services might affect crash risk: earnings management in tax expenses and tax avoidance. Also examined is whether the association between tax services and crash risk is moderated by the particular business strategy that organizations pursue. A two-stage model is used to control for the potential endogeneity inherent in the selection of auditors for tax services. Empirical findings reveal that auditor-provided tax services attenuate crash risk by constraining both earnings management in tax expenses and tax avoidance. Further evidence shows that auditor-provided tax services reduce crash risk for firms following innovator business strategies. Taken together, empirical findings reported in this study support knowledge spillover benefits, that is, insights gained from tax services can enhance audit effectiveness.